IMPROVING CRITICAL THINKING SKILL USING LITERATURE READING - Cita Hikmah Yanti (HOLISTICS, 2016)
This study was investigating the use of literature based instruction to develop students’ critical thinking.Some strategies were incorporated into the procedure of teaching and students were emphasized to think critically using questioning strategy. Sixty students of the fourth semester of English Education Study Program were involved and thirty of them were selected by using purposive sampling technique. This research was conducted for 30 meetings in three months. Non equivalent groups’ pretest- posttest-control group design was used in this research. Students took the pretest and posttest in the form of critical thinking test. The result showed that: 1) there was a significant improvement in critical thinking and, 2) there was also a significant mean difference between the experimental and control groups, 3) literature contributed about 98.9 % towards the students’ critical thinking. Thus, literature helps students to think more critically. Furthermore, for gaining better result, it is necessary to apply this method for longer time and help the students to form a good habit in reading.